Aplikasi Pemesanan Menu Menggunakan Metode RAD Studi Kasus Langkar Kopi - Kemal Indrawan (CV. Shofanah Media Berkah, 2023)
Langkar Kopi has a problem when customers who come together at the same time often have a queue of customers. Integrating QR Code technology into the menu serving management system in producing food/beverage customer orders to make it more effective and efficient. To overcome these problems researchers use QR Code scan technology to order food/beverage menus. Integrating QR Code technology into the serving menu management system in producing food/beverage customer orders to make it more effective and efficient. Then the system that will be made later is a menu ordering application using QR Code which will be implemented, to minimize customer queues that occur at the cashier. In this study, the authors used the Rapid Application Development method. for making its website, namely using the PHP programming language and the Codeigniter 3.0 Framework. as well as for the database using MySQL as database storage. With the existence of this system, it is hoped that it can help Langka Kopi in providing its services to customers.